2009
DOI: 10.1055/s-0029-1224162
|View full text |Cite
|
Sign up to set email alerts
|

Correlations and Discrepancies between Serum and Brain Tissue Levels of Neurotrophins after Electroconvulsive Treatment in Rats

Abstract: The time course of central and peripheral BDNF changes may significantly differ. However, we demonstrate substantial evidence that it can be justified to measure serum BDNF levels with a time delay to monitor brain tissue neurotrophin alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
141
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(148 citation statements)
references
References 44 publications
6
141
0
1
Order By: Relevance
“…68,69 There is evidence that peripheral NF concentrations are associated with brain tissue expression. 70 Indeed, cerebral BDNF crosses the blood-brain barrier, and it has been suggested that peripheral BDNF levels are correlated with brain tissue BDNF levels in rodents. 70 Moreover NGF, NT3, and NT-4/5 can cross the blood-brain barrier of mice in vivo to arrive at the brain parenchyma, and peripheral administration of neurotrophins could have neurobiological effects within the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68,69 There is evidence that peripheral NF concentrations are associated with brain tissue expression. 70 Indeed, cerebral BDNF crosses the blood-brain barrier, and it has been suggested that peripheral BDNF levels are correlated with brain tissue BDNF levels in rodents. 70 Moreover NGF, NT3, and NT-4/5 can cross the blood-brain barrier of mice in vivo to arrive at the brain parenchyma, and peripheral administration of neurotrophins could have neurobiological effects within the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…70 Indeed, cerebral BDNF crosses the blood-brain barrier, and it has been suggested that peripheral BDNF levels are correlated with brain tissue BDNF levels in rodents. 70 Moreover NGF, NT3, and NT-4/5 can cross the blood-brain barrier of mice in vivo to arrive at the brain parenchyma, and peripheral administration of neurotrophins could have neurobiological effects within the central nervous system. 71 However, plasma BDNF has been hypothesized to behave as a state-dependent marker, while serum BDNF might signify illness.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the strong correlation between decreases in serum BDNF concentration and changes in neuroplasticity strongly suggests that serum BDNF concentration reflects the presence of residual traces responsible for vulnerability to depression. Although the mechanisms allowing us to explain the relationship between serum and hippocampal BDNF are unknown, a recent study showed that measuring serum BDNF concentration can be used to monitor changes in neurotrophin levels in brain tissue (Sartorius et al, 2009). A decrease in serum BDNF concentration associated with normal serum cortisol concentration may be considered a relevant biomarker for identifying, within a population at risk, individuals more likely to develop depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, BDNF can readily cross the blood-brain barrier via a high-capacity transport system (Pan et al, 1998;Poduslo and Curran, 1996), serum BDNF correlates with cortical BDNF mRNA expression (Gervasoni et al, 2005), and serum BDNF may be affected by changes in cortical BDNF. For example, electroconvulsive treatments result in increased cortical BDNF followed by a rise in serum BDNF (Sartorius et al, 2009).…”
Section: Discussionmentioning
confidence: 99%